Radiation Toxins - Effects of Radiation Toxicity, Molecular Mechanisms of Action, Radiomimetic Properties and Possible Countermeasures for Radiation Injury - Popov, Dmitri; Jones, Jeffrey; Maliev, Vacheslav (IntechOpen, 2012)
None